Pengaruh E-Service Quality dan E-Trust Terhadap Kepuasan Pelanggan (Studi Pada Mahasiswa Universitas Majalengka Pelanggan E-Commerce Shopee) - haris Fauzi (Prodi Ekonomi Syariah Universitas Majalengka, 2021)
ABSTRACT The goal of this study was to see how much the quality of e-services has improved, e-trust and customer satisfaction at the University of Mayalengka is partially or partially. The research method used is a survey method with a descriptive and validation approach. This study included students from the University of Majalengka. The example is The total number of people who took part in this study was 100. The sampling technique used is targeted. The Likert measurement scale is used in this study. Validation and validation were the test tools employed in this investigation. The test for normality, multicollinearity, heteroscedasticity, and coefficient of determination were employed in this work to perform a conventional guess test, autocorrelation test, multiple linear regression analysis, model feasibility test, and hypothesis testing for some using t-test. The outcomes revealed that both the quality of e-services and e-trust had a significant impact in terms of client happiness. This means that the best e-service Keywords : e-service quality, e-trust, customer satisfaction